Feasibility Analysis of Indonesian Cellular Operator Consolidation Design - Ria Fistarini; Gunawan Wibisono (AIBPM Publisher, 2019)
The high population and increasing growth in the penetration of the use of cellular telecommunications services in Indonesia have encouraged businesses to provide cellular telecommunications services in Indonesia. There are seven existing cellular operators who compete in attracting customers by providing services and prices that are considered to satisfy the customers. However, if seen from the operational performances and financial performances of cellular operators in Indonesia, there is an unbalanced and unfair competition between cellular operators. Consolidation between cellular operators is one of the solutions offered in overcoming the problems of Indonesia's cellular telecommunications industry. In this paper, the consolidation of the four largest cellular operators in Indonesia, namely Telkomsel, ISAT, XL and Three will be designed and analyzed by using the data of operational performance and financial performance of the cellular operators. The operational performance data used as parameters are the number of customers and Base Transceiver Station (BTS) of each cellular operator. While the financial performance data used are the data in the financial statements to calculate the financial ratios of cellular operators so that they can be used as parameters to measure the feasibility of a business company. This consolidated design scenario is designed by combining a maximum of two cellular operators. The results of the study indicate that consolidated design that illustrates the business feasibility and efficiency of the cellular telecommunications industry is consolidation between Telkomsel - Three and ISAT - XL. The feasibility analysis of the consolidation of cellular operators is expected to provide benefits and suggestion in balancing competition in the cellular industry and can improve the efficiency of the telecommunications industry.